Gemtuzumab ozogamicin in NPM1-mutated acute myeloid leukemia: early results from the prospective randomized AMLSG 09-09 phase III study - Schlenk, Richard Friedrich; Paschka, Peter; Krzykalla, Julia; Weber, Daniela; Kapp-Schwoerer, Silke; Gaidzik, Verena I.; Leis, Claudia; Fiedler, Walter; Kindler, Thomas; Schroeder, Thomas; Mayer, Karin; Lübbert, Michael; et al. (Journal of clinical oncology, 2019)
PURPOSEHigh CD33 expression in acute myeloid leukemia (AML) with mutated NPM1 provides a rationale for the evaluation of gemtuzumab ozogamicin (GO) in this AML entity. We conducted a randomized trial to evaluate GO in combination with intensive induction and consolidation therapy in NPM1-mutated AML.PATIENTS AND METHODSBetween May 2010 and September 2017, patients ≥ 18 years old and considered eligible for intensive therapy were randomly assigned up front for induction therapy with idarubicin, cytarabine, etoposide, and all-trans-retinoic acid with or without GO. The early (P = .02) primary end point of event-free survival (EFS) was evaluated 6 months after completion of patient recruitment.RESULTSFive hundred eighty-eight patients were randomly assigned (standard arm, n = 296; GO arm, n = 292). EFS in the GO arm was not significantly different compared with that in the standard arm (hazard ratio, 0.83; 95% CI, 0.65 to 1.04; P = .10). The early death rate during induction therapy was 10.3% in the GO arm and 5.7% in the standard arm (P = .05). Causes of death in both arms were mainly infections. The cumulative incidence of relapse (CIR) in patients achieving a complete remission (CR) or CR with incomplete hematologic recovery (CRi) was significantly reduced in the GO arm compared with the standard arm (P = .005), with no difference in the cumulative incidence of death (P = .80). Subgroup analysis revealed a significant beneficial effect of GO in female, younger (≤ 70 years), and FLT3 internal tandem duplication-negative patients with respect to EFS and CIR.CONCLUSIONThe trial did not meet its early primary end point of EFS, mainly as a result of a higher early death rate in the GO arm. However, in patients achieving CR/CRi after induction therapy, significantly fewer relapses occurred in the GO compared with the standard arm.